Psychometric Properties of the BAASIS: A Meta-analysis of Individual Participant Data - Denhaerynck, Kris; Dobbels, Fabienne; Košťálová, Barbora; De Geest, Sabina (Transplantation, 2023)
BACKGROUND: Nonadherence to immunosuppressives, a risk factor for poor posttransplant outcomes, can be assessed by self-report using the Basel Assessment of Adherence to Immunosuppressive Medications Scale (BAASIS). Available in written and interview versions, and previously validated on content, the BAASIS is widely used in research and clinical practice. The aim of this study was to investigate its psychometric properties. METHODS: Using a literature search and our BAASIS database, this meta-analysis identified completed studies in adult transplant recipients whose data were usable to examine the BAASIS' reliability and 3 validity aspects: (1) relationships with other variables (electronic monitoring, other self-report scales, tacrolimus blood-level variability, collateral report, depressive symptoms, psycho-behavioral constructs, and interventions); (2) response processes; and (3) internal structure. Testing used random-effects logistic regressions. RESULTS: Our sample included 12 109 graft recipients from 26 studies. Of these 26, a total of 20 provided individual participant data. Evidence of the BAASIS' stability over time supports its reliability. Validity testing of relationships with other variables showed that BAASIS-assessed nonadherence was significantly associated with the selected variables: electronically monitored nonadherence ( P < 0.03), other self- and collaterally-reported nonadherence ( P < 0.001), higher variability in tacrolimus concentrations ( P = 0.02), higher barriers ( P < 0.001), lower self-efficacy ( P < 0.001), lower intention ( P < 0.001), and higher worries ( P = 0.02). Nonadherence also decreased after regimen change interventions ( P = 0.03). Response process evaluation indicated good readability and slightly higher nonadherence with the written version. Structurally, items on taking and timing shared variability. CONCLUSIONS: The BAASIS shows good validity and reliability as a self-report instrument to assess medication nonadherence in transplantation.
Keywords: dospělí; Reproducibility of Results; Medication Adherence; takrolimus; lidé; reprodukovatelnost výsledků; adherence k farmakoterapii; Psychometrics; zpráva o sobě; Immunosuppressive Agents; Self Report; psychometrie; Tacrolimus; imunosupresiva; Adult; Humans